The Influence of the E-Performance System and Leadership on Employee Performance: Work Discipline as an Intervening Variable - Andika, Afri; Rahmawati, Reni (UPI YPTK Journal of Business and Economics, 2025)
This research aims to discover the influence the E-Kinerja and Leadership System has on employee performance with the intervening variable Work Discipline at PT. Mutiara Agam Tiku V Jorong, Agam Regency. The data collection method is through surveys and distributing questionnaires, with a sample of 100 respondents. The analysis method used is path analysis using SMARTPLS 3. The research results showed that the E-Kinerja System had a positive and significant effect on Work Discipline. Leadership had a positive and significant effect on Work Discipline. The E-Kinerja system has a positive and significant effect on employee performance. Leadership has a positive and significant effect on employee performance. Work Discipline does not have a positive and significant influence on employee performance. Work Discipline does not mediate the influence of the E-Kinerja System on employee performance. Work Discipline does not mediate the influence of Leadership on employee performance. The contribution of the independent variables E-Kinerja System, Leadership and Work Discipline to the dependent variable Employee Performance is 83.6%. Meanwhile, the remaining 16.4% is influenced by other variables outside this research